2014
DOI: 10.1002/dmrr.2585
|View full text |Cite
|
Sign up to set email alerts
|

Advanced complicated diabetes mellitus is associated with a reduced risk of thoracic and abdominal aortic aneurysm rupture: a population‐based cohort study

Abstract: Our results demonstrate that patients with diabetes in this Asian population have reduced prevalence of thoracic and abdominal aortic aneurysms. The observed paradoxical inverse relationship between severity of DM and aortic aneurysms is clear. Further research is required to investigate the underlying mechanisms for the reduced risk of aortic aneurysms associated with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 49 publications
5
67
0
Order By: Relevance
“…Of 100 potentially relevant articles screened initially, nine eligible studies 8,[11][12][13][14][15][16][17][18] were identified. Furthermore, two relevant studies 6,7 were added through a manual search.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 100 potentially relevant articles screened initially, nine eligible studies 8,[11][12][13][14][15][16][17][18] were identified. Furthermore, two relevant studies 6,7 were added through a manual search.…”
Section: Resultsmentioning
confidence: 99%
“…In total, our meta-analysis included 11 studies. [6][7][8][11][12][13][14][15][16][17][18] Study design (Table 1), patient characteristics (Table 1; online Appendices 1 and 2), diabetes prevalence, rupture incidence and relative risk of rupture are summarized in Table 2. In a case-control study by Buijs et al, 11 non-ruptured symptomatic AAA and ruptured AAA were combined and labelled as non-elective AAA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations